2010
DOI: 10.1063/1.3460594
|View full text |Cite
|
Sign up to set email alerts
|

Embedding theory for excited states

Abstract: Using the technique of Perdew and Levy [Phys. Rev. B 31, 6264 (1985)], it is shown that both the density function theory (DFT)-in-DFT and wave function theory (WFT)-in-DFT embedding approaches are formally correct in studying not only the ground state but also a subset of the excited states of the total system. Without further approximations, the DFT-in-DFT embedding approach results in a pair of coupled Euler-Lagrange equations. In contrast to DFT-in-DFT, the WFT-in-DFT approach is shown to ensure a systemati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
66
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(66 citation statements)
references
References 21 publications
(18 reference statements)
0
66
0
Order By: Relevance
“…Following the Levy-Perdew theorem, 4 other than the lowest energy solutions of the Euler-Lagrange equation of FDET can be associated with excited states as noticed by Khait and Hoffmann. 5 Without further approximations concerning the FDET embedding potential, FDET based methods feature a qualitative difference from most of other embedding methods used in practice -the FDET embedding potential depends on the embedded density (ρ A (⃗ r)). This leads to the following practical consequences.…”
Section: Introductionmentioning
confidence: 99%
“…Following the Levy-Perdew theorem, 4 other than the lowest energy solutions of the Euler-Lagrange equation of FDET can be associated with excited states as noticed by Khait and Hoffmann. 5 Without further approximations concerning the FDET embedding potential, FDET based methods feature a qualitative difference from most of other embedding methods used in practice -the FDET embedding potential depends on the embedded density (ρ A (⃗ r)). This leads to the following practical consequences.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, WFT-in-DFT embedding utilizes the theoretical framework of DFT embedding to enable the WFT description of a given subsystem in the effective potential that is created by the remaining electronic density of the system. [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] We recently introduced a simple, projection-based method for performing accurate WFT-in-DFT embedding calculations 30 that avoids the need for a numerically challenging optimized effective potential (OEP) calculation 24,25,[31][32][33][34] via the introduction of a level-shift operator. It was shown that this method enables the accurate calculation of WFT-in-DFT subsystem correlation energies, as well as many-body expansions (MBEs) of the total WFT correlation energy.…”
Section: Introductionmentioning
confidence: 99%
“…Among these are the QM/MM, [1][2][3][4][5][6] ONIOM, 7,8 fragment molecular orbital (FMO), [9][10][11][12][13][14][15] and wavefunction theory (WFT)-in-density functional theory (DFT) embedding [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] approaches, which allow for the treatment of systems that would not be practical using conventional WFT approaches. In particular, WFT-in-DFT embedding utilizes the theoretical framework of DFT embedding to enable the WFT description of a given subsystem in the effective potential that is created by the remaining electronic density of the system.…”
Section: Introductionmentioning
confidence: 99%
“…[25][26][27][28] It can be shown that using such an embedding potentials is formally exact (i.e., it is exact if the exact exchangecorrelation and kinetic-energy functionals are used and the limit of an exact WFT description is reached). 65,66 In ref. 33, three of us proposed a simplified scheme for the calculation of local excitation energies with WFT-in-DFT embedding.…”
Section: Wft-in-dft Embeddingmentioning
confidence: 99%